Dentin hypersensitivity: knowledge, attitudes, and management strategies - cross-sectional, in vitro, and randomized controlled clinical trial studies with polymeric and fluoride-containing materials - Mosquim, Victor (2024)
This study aimed to investigate (1) the knowledge of Brazilians, (2) undergraduates and dentists on prevention, diagnosis, and management of dentin hypersensitivity (DH); (3) whether three monomeric agents could reduce the hydraulic conductance (Lp) of dentin; (4) the efficiency of a TiF4 varnish, NaF varnish, a SnCl2+chitosan+AmF toothpaste and a FCPS-containing toothpaste in reducing the Lp of dentin; (5) whether the TiF4 varnish, the NaF varnish, a SnCl2+chitosan+AmF-containing toothpaste, and a FCPS-containing toothpaste are clinically effective for managing DH, and their impact on oral health-related quality of life (OHRQoL). Questionnaires investigated the (1) oral health self-perception and attitudes, and DH prevention and management measures of 226 participants; and (2) attitudes and knowledge of 132 undergraduates and 338 dentists. Data were analyzed by a multiple linear regressions (<0.05). In vitro, the Lp of dentin were measured with (LpMin) and without (LpMax) smear layer, after treatment (LpTreat) with (3) Gluma Desensitizer, PRG Barrier Coat (PBC), Icon infiltrant, (4) NaF varnish, TiF4 varnish, SnCl2+chitosan+AmF toothpaste and a FCPS-containing toothpaste, and after erosion (LpEro). Laser scanning confocal microscopy (LSCM) was performed. The light-curable products degree of conversion were calculated. Data were subjected to 2-way repeated measures ANOVA, paired t-test, and to t-test (<0.05). In a randomized clinical trial (RCT) (5), fifty-one patients/241 teeth were randomized into four groups. DH was measured using a visual analog scale (VAS) after evaporative and tactile stimuli at baseline, immediately after application, after 1, 3, and 6 months. One-way ANOVA, Fishers exact test, Kruskal-Wallis, Friedmans test, and two-way repeated measures ANOVA ( = 0.05) were used. Results evidenced that (1) participants rarely or never scheduled appointments after experiencing DH. (2) Self-reported knowledge of DH was higher than actual knowledge for undergraduates and dentists, with highest scores for dentists. Gingival recession and acidic diet were major risk factors. Students managed DH with dietary/hygiene advice plus desensitization, while dentists used occlusal adjustments. Most participants could not distinguish DH from caries or hypomineralization. (3) Icon showed the lowest LpTreat and LpEro values. Icon and PBC showed LpEro similar to LpMin. More mineral deposition was noticeable for PBC. Gluma presented the deepest penetration in dentin. The degree of conversion of PBC was the highest. (4) The FCPS toothpaste presented lower Lp values than the TiF4 varnish and the SnCl2+chitosan+AmF toothpaste. Only the FCPS toothpaste reduced the LpTreat and LpEro. LSCM evidenced more deposits for both toothpastes. (5) In the RCT, all products reduced VAS scores, with the SnCl2+chitosan+AmF toothpaste being superior to the NaF varnish at 6 months for evaporative stimulus. No difference was observed at 6 months for the tactile stimulus. In conclusion, 36.7% and 18.6% of patients were unaware that DH can be prevented and treated, respectively. Both students and dentists overestimate their DH knowledge. Icon showed the greatest reduction in Lp. PBC was more effective after erosion. FCPS toothpaste reduced dentin Lp, but all products created deposits. All products provided pain relief. Sn-containing toothpaste was superior to NaF varnish at 6 months, with all products equally improving OHRQoL.